Histopathological Evaluation of Post-Operative Biopsies in Oral Squamous Cell Carcinoma - Abedin, Md Jainul; Rahaman , Muhammad Mizanur; Rabby, Md Atiqul Islam; Hosen, Md Ikbal; Rahman, Md Zahedur; Rony, Md Fakrul Hassan; Hoshain (Hasan), Md Forhad; Parvin, Naznin (Medicine Today, 2026)
Introduction with Objective: The aim of the present study was to assess the Histopathological Evaluation of Post-Operative Biopsies in Oral Squamous Cell Carcinoma. Materials and Methods: This cross-sectional study was conducted from January 2020 to December 2021 in the oral and maxillofacial surgery department, DDCH. A total 85 cases were selected as study population as per inclusion and exclusion criteria. After data collection and processing, all statistical analysis were done by SPSS software windows version 29. Result: A large proportion of patients were diagnosed at an advanced stage, with 62.35% in Stage IV. Perineural invasion was present in 30.5% of cases, and lymphovascular invasion was seen in 31.8%. Histologically, the majority of cases were Grade I (76.4%), and Anneroth's Grade II (40%) was the most common. Adjacent bone involvement was found in 37.6% of cases, while 20% of patients exhibited tumor necrosis. Salivary gland involvement was noted in 17.6% of cases. Pathological TNM staging revealed the highest number of patients in the PT4aN0Mx group (19.10%) and the N0 group (48.23%). The study also examined the depth of invasion, with most cases falling between 1-9 mm (18.82%) and 10-19 mm (18.82%). Extranodal extension was present in 12 cases, and several statistically significant associations were found between histopathological features, such as the highly significant relationship between perineural invasion and bony involvement. Conclusion: In conclusion, this study identifies key socio-demographic and clinical traits of oral cancer patients, revealing frequent perineural, lymphovascular, and bone involvement that indicate the disease’s aggressive nature. Medicine Today 2026, Vol.38 (1): 60-64